Calculus of thought : neuromorphic logistic regression in cognitive machines - Rice, Daniel M. (Waltham, Mass. : Academic Press, an imprint of Elsevier, 2014)
A must-read for all scientists about a very simple computation method designed to simulate big-data neural processing. This book is inspired by the Calculus Ratiocinator idea of Gottfried Leibniz, which is that machine computation should be developed to simulate human cognitive processes, thus avoiding problematic subjective bias in analytic solutions to practical and scientific problems. The reduced error logistic regression (RELR) method is proposed as such a'Calculus of Thought.'
Includes bibliographical references and index.
Keywords: Computational neuroscience; Cognitive science -- Mathematical models